ALTERNATIVE TO Q WAVE DIAGNOSIS USING CARDIAC ACTION POTENTIAL PROPAGATION TIME MEASUREMENT - S. Ananthi; V. Vignesh; K. Padmanabhan (Российский кардиологический журнал, 2016)
The diagnosis of myocardial infarction is done by ECG through the observation of Q waves in one or more leads. The paper describes the relationship between Q waves and the propagation time of the Cardiac Action potential and a technique by which this time of propagation itself can be measured. Rather than observing the Q wave pathology in its very small peak of the total QRS complex, a more refined method is thus made available for continuous patient observation. This propagation time rises from 15 ms to 35 ms or more in progressive pathological conditions. A simulation has been done which illustrates how the Q wave is generated from the travelling action potential wave in the ventricle. The authors have utilized the easy to use novel EPIC Microelectrodes from Plessey Electronics, which are jelly free and provide easy attachment by simple skin contact. Multiple sensors were placed on the chest and the propagation time was measured by differential voltages between them. An embedded controller was used to pick these signals in digitized form and calculate the time intervals. The measurement procedure is simple and highly non invasive. Records from outpatients with cardiac pathology were taken and it was verified that this AP time increases with the Q wave width. This AP propagation time is a more refined method of observing pathological changes than the Q wave, since progressive changes in cardiac condition can be indicated by changes in the millisecond values. It has been verified that the values match with to the usual Q wave width timings.